ANALISIS SERVICE EXPERIENCE DALAM MENCIPTAKAN KEPUASAN PENUMPANG KERETA WISATA PT. KERETA API PARIWISATA (Survei Pada Wisatawan Domestik Kereta Wisata Bali, Kereta Wisata Toraja, Kereta Wisata Nusantara PT. Kereta Api Pariwisata) - Sari, Wulan; Wibowo, Lili Adi; siswhara, Gita (Universitas Pendidikan Indonesia, 2016)
PT. Kereta Api Pariwisata is one of subsidiaries of PT. Kereta Api Indonesia (Persero), which manages business travel services and tour-based railroad. PT. Kereta Api Pariwisata has thre tourism trains such Bali tourism train, Toraja tourism train, and Nusantara tourism train. The third tourism train offers comfort and beauty of the theme of culture of Bali, Toraja, and Nusantara that can provide a service experience to passengers is expected to create a tourism train passenger satisfaction PT. Kereta Api Pariwisata. The theory of service experience that is used by Knutson et al., In Identifying the Dimensions of the Experience Construct. Journal of Hospitality Leisure Marketing (2006:39) with dimensions used are incentive, accessibility, convenience, utility, environment, benefits, and trust. Theory of satisfaction is a composite theory of Kotler (2009:164) with dimensions of performance and importance to the theory Hatane Semuel (2009:30) which states